Intestinal microbiota changes pre- and post-fecal microbiota transplantation for treatment of recurrent Clostridioides difficile infection among Iranian patients with concurrent inflammatory bowel disease - Gholam-Mostafaei, Fahimeh Sadat; Azimirad, Masoumeh; Naseri, Kaveh; Nabavi-Rad, Ali; Asadzadeh Aghdaei, Hamid; Shahrokh, Shabnam; Ebrahimi Daryani, Nasser; Yadegar, Abbas; Zali, Mohammad Reza (Frontiers in Microbiology, 2023)
Patients with inflammatory bowel disease (IBD) are at a greater risk for the recurrence of Clostridioides difficile infection (rCDI) that is triggered by intestinal microbiota dysbiosis. Fecal microbiota transplantation (FMT) has emerged as a highly effective therapeutic option for this complication. However, little is known about the impact of FMT on intestinal microbiota alterations in rCDI patients suffering from IBD. In this study, we aimed to investigate post-FMT intestinal microbiota alterations in Iranian rCDI patients with underlying IBD. A total of 21 fecal samples were collected including 14 samples pre- and post-FMT and 7 samples from healthy donors. Microbial analysis was performed by quantitative real-time PCR (RT-qPCR) assay targeting the 16S rRNA gene. The pre-FMT profile and composition of the fecal microbiota were compared to the microbial changes of samples collected 28 days after FMT. Overall, the fecal microbiota profile of recipients was more similar to donor samples after the transplantation. We observed a significant increase in the relative abundance of Bacteroidetes post-FMT, compared to the pre-FMT microbial profile. Furthermore, there were remarkable differences between the microbial profile of pre-FMT, post-FMT, and healthy donor samples by PCoA analysis based on the ordination distance. This study demonstrates FMT as a safe and effective approach to restore the indigenous composition of the intestinal microbiota in rCDI patients and ultimately results in the treatment of concurrent IBD.